Antibody‐based methods for the measurement of α‐synuclein concentration in human cerebrospinal fluid – method comparison and round robin study. Issue 1 (13th November 2018) - Mollenhauer, Brit; Bowman, Frederick DuBois; Drake, Daniel; Duong, Jimmy; Blennow, Kaj; El‐Agnaf, Omar; Shaw, Leslie M.; Masucci, Jennifer; Taylor, Peggy; Umek, Robert M.; Dunty, Jill M.; Smith, Chris L.; et al.
Abstract : α‐Synuclein is a synaptic protein that forms intracellular Lewy body inclusions in Parkinson's disease and other so called synuclein aggregation disorders. There are several methods to measure α‐synuclein concentration in human cerebrospinal fluid, where it is a candidate diagnostic and prognostic biomarker. In the current paper, we compared the analytical characteristics of four immunochemical (MSD, BioLegnd, Adx, and Roche) and one mass spectrometry‐based method. Variance component analysis partitions the total variance associated with 49 sample measured by site, kit lot, and replicate. The results show that the different methods measure similar forms of α‐synuclein and that a common reference material would allow for assay harmonization, which will be important in studies evaluating drugs that target α‐synuclein pathology specifically. Abstract: α‐Synuclein is the major component of Lewy bodies and a candidate biomarker for neurodegenerative diseases in which Lewy bodies are common, including Parkinson's disease and dementia with Lewy bodies. A large body of literature suggests that these disorders are characterized by reduced concentrations of α‐synuclein in cerebrospinal fluid (CSF), with overlapping concentrations compared to healthy controls and variability across studies. Several reasons can account for this variability, including technical ones, such as inter‐assay and inter‐laboratory variation (reproducibility). We compared four immunochemical methods for the quantification of α‐synuclein concentration in 50 unique CSF samples. All methods were designed to capture most of the existing α‐synuclein forms in CSF ('total' α‐synuclein). Each of the four methods showed high analytical precision, excellent correlation between laboratories ( R 2 0.83–0.99), and good correlation with each other ( R 2 0.64–0.93), although the slopes of the regression lines were different between the four immunoassays. The use of common reference CSF samples decreased the differences in α‐synuclein concentration between detection methods and technologies. Pilot data on an immunoprecipitation mass spectrometry (IP‐MS) method is also presented. Our results suggest that the four immunochemical methods and the IP‐MS method measure similar forms of α‐synuclein and that a common reference material would allow harmonization of results between immunoassays.